(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes the coverage of psychological culture issues in the scientific research of our country’s scholars. It examines the role of psychological culture in society, the factors influencing its formation, and its significance in youth upbringing from a theoretical perspective. The article also highlights the impact of psychological culture on personal development and explores ways to enhance it based on various studies. The results of research conducted in our country using modern psychological approaches are analyzed, and recommendations for future studies are provided.